BODY DISSATISFACTION DAN SELF-ESTEEM: STUDI KORELASIONAL PADA PEREMPUAN EMERGING ADULTHOOD - Joan Andriona; Pamela Hendra Heng; Hanna Christina Uranus (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT The increasing phenomenon of body dissatisfaction among women in emerging adulthood is often associated with the development of self-esteem. Body dissatisfaction is defined as a negative perception of body shape or size, accompanied by feelings of discomfort and dissatisfaction with physical appearance, whereas self-esteem refers to an individual’s overall evaluation of self-worth and self-acceptance. This study aimed to examine the relationship between body dissatisfaction and self-esteem levels among women in emerging adulthood. A quantitative correlational approach was employed, involving 338 female participants aged 18–25 years who were selected using purposive sampling. Data were collected using the Body Shape Questionnaire (BSQ-34) and the Indonesian-adapted version of the Rosenberg Self-Esteem Scale. The results indicated a significant negative relationship between body dissatisfaction and self-esteem (r = ?0.496). Additional analyses revealed significant differences in body dissatisfaction and self-esteem based on body mass index (BMI) categories, with the majority of participants falling within the moderate level for both variables. These findings highlight the importance of a healthy and positive body perception in supporting the development of adaptive self-esteem among women in emerging adulthood. Future research is recommended to include other psychological variables or moderating factors to obtain a more comprehensive understanding of the determinants of self-esteem. ABSTRAK Fenomena meningkatnya ketidakpuasan tubuh (body dissatisfaction) pada perempuan usia emerging adulthood kerap dikaitkan dengan pembentukan harga diri (self-esteem). Body dissatisfaction dipahami sebagai persepsi negatif terhadap bentuk atau ukuran tubuh yang disertai rasa tidak nyaman dan ketidakpuasan terhadap penampilan fisik, sedangkan self-esteem merujuk pada penilaian individu terhadap nilai serta penerimaan diri secara keseluruhan. Studi ini bertujuan untuk menguji hubungan antara body dissatisfaction dan tingkat self-esteem pada perempuan emerging adulthood. Pendekatan kuantitatif korelasional digunakan dengan melibatkan 338 partisipan perempuan berusia 18–25 tahun yang dipilih melalui teknik purposive sampling. Pengumpulan data dilakukan menggunakan instrumen Body Shape Questionnaire (BSQ-34) dan Rosenberg Self-Esteem Scale dalam adaptasi Bahasa Indonesia. Hasil analisis menunjukkan adanya hubungan signifikan antara body dissatisfaction dan self-esteem (r = -0.496). Analisis tambahan juga menemukan perbedaan signifikan body dissatisfaction dan self-esteem berdasarkan kategori indeks massa tubuh (BMI), dengan mayoritas partisipan berada pada kategori tingkat sedang untuk kedua variabel. Temuan ini menegaskan pentingnya persepsi tubuh yang sehat dan positif dalam mendukung pembentukan self-esteem yang adaptif pada perempuan emerging adulthood. Penelitian selanjutnya disarankan untuk melibatkan variabel psikologis lain atau faktor moderator guna memperoleh pemahaman yang lebih komprehensif mengenai determinan self-esteem.